Model for Improving Employee Performance Through Workload and Work-Life Balance of Employees at PT PLN (Persero) UP3 Balikpapan - Mochamad Alfian Nanda Pratama; Sri Wahyuni Ratnasari (Universitas KH. Abdul Chalim Mojokerto, 2025)
Employee performance in a company has an important factor, management must monitor the performance of all employees to ensure the best performance. An increase or decrease in employee performance can be influenced by various factors, including external factors including workload and work-life balance. Providing a workload that meets standards can support the achievement of optimal employee performance, and employee balance at work needs to be improved so that employees have optimal performance. The type of research used in this research is explanatory research. This research took place at PT PLN (Persero) UP3 Balikpapan with a research sample of 130 employees. The data collection technique uses a questionnaire. In this research, data analysis uses the SEM-PLS method with SmartPLS (Partial Least Squares) software. Research results 1) Workload has a negative and significant effect on employee performance. Based on the p-value of 0.004 < 0.05 plus the T-Statistics value (2.857) > 1.96, the original sample value is 0.258 (negative). 2) The workload has a negative and significant effect on work-life balance. Based on the P-Values ​​value of 0.002 < 0.05 and the t-statistics value (3.226) > 1.96), the original sample value is 0.327 (negative). 3) Work-life balance has a positive and significant effect on employee performance. Based on the P-value ​of 0.000 <0.05 and the T-Statistics value (4.695)>1.96, the original sample value is 0.353 (positive). 4) Work-life balance is able to mediate the influence of workload on employee performance based on the P-values ​​specific indirect effect value of 0.023 < 0.05 and t-statistic value (2.177) > 1.96).